Diimide hydrogenation of isoprene-styrene diblock copolymers - Pranee Phinyocheep (2018)
Isoprene-styrene diblock copolymers of various molecular weights were prepared by anionic polymerization with n-BuLi in cyclohexane. Hydrogenation of the unsaturated backbone of the block copolymers was performed with diimide generated in situ by the thermolysis of p-toluenesulfonylhydrazide (TSH). The reaction was carried out in xylene at 135°C. A molar ratio of TSH to double bonds equal to 4:1 was found to be the optimum ratio, which provided the highest percentage of hydrogenation. The percentage of hydrogenation analyzed by 1H-NMR, IR spectroscopy, and iodine value (the Wijs method) were compared. Evidence from 1H-NMR also revealed a change in the ratio of the cis-trans configuration after hydrogenation. The thermal stability of the hydrogenated products was improved as shown by the results from thermogravimetric analysis. From differential scanning calorimetry measurements, the glass-transition temperatures of the hydrogenated products were found to increase about 10-20°C above those of the original block copolymers. © 2002 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 87.